An Instructional Design Process for Developing Students Higher Order Thinking Skills in Number Patterns - Muiz Ghifari (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2021)
Higher order thinking skills in learning are the application of thinking processes for complex situations and of course have many variables. Every student can think, but most students need encouragement and guidance for higher order thinking processes. The research used a qualitative approach, namely literature review. This study aims to explain the outline of activities planned for designing learning on number pattern class VIII material, the development of learning objectives, expected results, and practice questions that require the use of high order skills. Several efforts must be made to improve students' higher order thinking skills in mathematics, namely: (1) involving students in non-routine problem solving activities; (2) facilitating students to develop their ability to analyze and evaluate (critical thinking) and creative ability (creative thinking); and (3) encourage students to construct their own knowledge, so that learning becomes meaningful for students.